If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 3(-6x + 7) Reorder the terms: 7 = 3(7 + -6x) 7 = (7 * 3 + -6x * 3) 7 = (21 + -18x) Solving 7 = 21 + -18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18x' to each side of the equation. 7 + 18x = 21 + -18x + 18x Combine like terms: -18x + 18x = 0 7 + 18x = 21 + 0 7 + 18x = 21 Add '-7' to each side of the equation. 7 + -7 + 18x = 21 + -7 Combine like terms: 7 + -7 = 0 0 + 18x = 21 + -7 18x = 21 + -7 Combine like terms: 21 + -7 = 14 18x = 14 Divide each side by '18'. x = 0.7777777778 Simplifying x = 0.7777777778
| 3k+8=17 | | x^2+9x+10= | | 8(x+6)-4= | | R-24=-14 | | t(3t-2)=0 | | (-75)=25 | | 4x(2)=16 | | 2x-4=9x-35 | | (75)=25 | | 5x+5=115+x | | 2x^2+18x+36= | | 71-7x=29x+19x | | 4-c=16 | | 3x^2-16x-35= | | 168=3x-12 | | -100-8x=9x+19x | | 6x^2-x-7= | | X^2+2x-48=4x-24 | | 168=12-3x | | 6(1-m)=10-2m | | 9x-7+11x-27=180 | | 143-5x=3x+23 | | 62=2(3+6x)+2(x) | | 12(5h-2)=5h+8 | | 3k-13=2(3k-5) | | -x+4(x-1)=12+x | | 3x-9x-7=-6x+2-7 | | 3x-5=2x+x-7 | | 50=2(4+6x)+2(x) | | -8(n-1)=13-7n | | 3x(2)=12 | | 8(-2-4)+12=-52 |